Creating Substantive Justice in State Administrative Courts: A Theoretical, Philosophical, and Human Rights Review - Alfons, Saartje Sarah; Soplanit, Miracle; Mail, Syed Muhammad Huzaif (Jurnal Suara Hukum, 2024)
Substantive justice in Administrative Court (PTUN) can be achieved through theoretical, philosophical, and human rights (HAM) approaches that ensure access to fair and equal justice, so that decisions made are not only procedurally valid but also reflect genuine justice for society. The objective of this research is to analyze how substantive justice can be realized in the practice of Administrative Court (PTUN) through theoretical, philosophical, and human rights approaches, as well as to explore the role of human rights in ensuring the achievement of substantive justice in administrative court proceedings. This research employs normative legal methods with legislative, philosophical, and human rights approaches, using literature study techniques and descriptive analysis of legislation, court decisions, and legal literature. The findings reveal that substantive justice in Administrative Court (PTUN) can be realized through the integration of theoretical, philosophical, and human rights (HAM) approaches to ensure justice transcends formal procedures and reflects true justice values. The theoretical approach encompasses natural law principles and distributive justice theory to balance individual rights and governmental authority, while the philosophical perspective adopts John Rawls' "justice as fairness" concept and Pancasila values emphasizing the balance of rights and obligations. The human rights approach ensures protection against arbitrary administrative actions, equal access to justice, and the right to a fair trial. However, the implementation of substantive justice in PTUN still faces challenges, such as the dominance of formalistic legal positivism, the limited understanding of judges regarding substantive justice principles, and unequal access to legal assistance for the underprivileged